Enhancing Students’ Learning Motivation via Community-Based Educational Counselings in STIT Al-Ittihadiyah Labuhanbatu Utara - Mira Tania (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
Student motivation is a fundamental aspect of academic success, especially in higher education environments where learners often face a range of personal and academic challenges. This study explores the implementation of a community-based educational counseling program designed to enhance students’ learning motivation at STIT Al-Ittihadiyah Labuhanbatu Utara. Using a mixed-methods approach, the study involved 60 undergraduate students who participated in an eight-week series of counseling sessions focused on motivational strategies, goal setting, and peer support. Quantitative data were collected through pre- and post-intervention questionnaires based on the Motivated Strategies for Learning Questionnaire (MSLQ), while qualitative insights were gathered via focus group discussions. The results showed significant improvements in intrinsic motivation, task value, and self-efficacy, alongside a reduction in test anxiety. Students also reported a greater sense of belonging, emotional resilience, and academic purpose. The findings suggest that community-based counseling is an effective and culturally responsive approach to fostering student motivation and can be a valuable model for institutions in similar educational contexts.